Potensi Bubuk Stroberi terhadap Biomarkers Kardiometabolik dan Metabolik pada Dewasa dengan Obesitas: Scoping Review: The Potential of Strawberry Powder on Cardiometabolic and Metabolic Biomarkers in Adults with Obesity: A Scoping Review - Fadhilah, Azzahra Nur; Nurwati, Ida; Rahardjo, Setyo Sri (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Obesity was a condition of fat accumulation in the body due to an imbalance of energy intake and energy expended over a long period. Data showed that the prevalence of obesity continued to increase worldwide and in Indonesia. Obesity conditions were associated with various risks of degenerative diseases, characterized by poor metabolic examination results in the obese group. Strawberry fruit contained rich polyphenols and antioxidants, which had the potential to be a dietary therapy for obese groups in the form of strawberry powder. Researchers needed to study further by exploring the possibility of strawberry powder to improve obesity-related biomarkers. This study referred to the scoping review guide by using the PCC (Population, Concept, and Context) framework to determine the scope of exploration and used the PRISMA diagram as a tool for selecting articles to be reviewed. The search yielded 1678 articles (database: PubMed, Scopus, Science Direct) and were then eliminated according to the inclusion and exclusion criteria until the final extraction of 4 articles for review. Consumption of strawberry powder had positive effects on vascular function, endothelial function, cardiovascular function, lipid metabolism, as well as insulin sensitivity, and overall had the potential to improve metabolic biomarkers in obese groups.